2018
DOI: 10.1016/j.cyto.2017.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise inhibits obesity-induced respiratory phenotype

Abstract: Aerobic exercise reduces high fat diet-induced obese lung phenotype (AHR, pulmonary remodeling and inflammation), involving anti-inflammatory cytokine IL-10 and adiponectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The functional and structural alterations observed in the lungs (airways and parenchyma), in older adults with MS suggest that the lung may be a potential target organ in older adults in the setting of MS. The increases in airway and tissue resistance in the lungs, indicating the process of remodeling, is characterized by the accumulation of extracellular matrix proteins (collagen, elastin, proteoglycans, laminins) and reflect the structural and functional alterations in the lungs 9 . The alterations of the inflammatory milieu in the lungs are considered a causative factor in its remodeling process 9 , 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional and structural alterations observed in the lungs (airways and parenchyma), in older adults with MS suggest that the lung may be a potential target organ in older adults in the setting of MS. The increases in airway and tissue resistance in the lungs, indicating the process of remodeling, is characterized by the accumulation of extracellular matrix proteins (collagen, elastin, proteoglycans, laminins) and reflect the structural and functional alterations in the lungs 9 . The alterations of the inflammatory milieu in the lungs are considered a causative factor in its remodeling process 9 , 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The increases in airway and tissue resistance in the lungs, indicating the process of remodeling, is characterized by the accumulation of extracellular matrix proteins (collagen, elastin, proteoglycans, laminins) and reflect the structural and functional alterations in the lungs 9 . The alterations of the inflammatory milieu in the lungs are considered a causative factor in its remodeling process 9 , 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible positive effect of physical exercise in people with sarcoidosis is likely to be complex and depend on several pathways. Experimental studies performed on mice have shown that training induces alterations in peripheral blood lymphocyte subpopulations [35] and in mice with obesityrelated airway hyper-responsiveness, training induced a reduction of several inflammatory cells (including lymphocytes) as well as pro-inflammatory cytokines in BALF [36]. T regulatory cells (T regs ) normally dampen the release of proinflammatory cytokines and thereby have a potential function in controlling and ending immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of regular physical exercise has beneficial effects for the integral health of the human being, in the physical sphere (Comin et al, 2018;Liu et al, 2018;Foright et al, 2018;Wiklund, 2016), mental (Colledge et al, 2018;Alonso-Patiño et al, 2013;Revnic et al, 2013) and socio-affective (Baillot et al, 2018;Rammant et al, 2017;Womble et al, 2014).…”
Section: Introductionmentioning
confidence: 99%